Winter Green Manure Decreases Subsoil Nitrate Accumulation and Increases N Use Efficiencies of Maize Production in North China Plain - Zonghui Hu; Qiu Zhao; Xinjian Zhang; Xiaoguang Ning; Hao Liang; Weidong Cao (Plants, 2023)
Planting a deep-rooted green manure (GM) (more than 1.0 m depth) greatly improves soil fertility and reduces the loss of nutrients. However, few studies have examined the response of soil nitrogen (N) distribution in the soil profile and subsoil N recovery to the long-term planting and incorporation of deep-rooted GM. Based on a 12-year (2009–2021) experiment of spring maize-winter GMs rotation in the North China Plain (NCP), this study investigated the effects of different GMs that were planted over the winter, including ryegrass (RrG, Lolium L.) (>1.0 m), Orychophragmus violaceus (OrV, Orychophragmus violaceus L.) (>0.8 m), and hairy vetch (VvR, Vicia villosa Roth.) (>1.0 m), on the spring maize yield, N distribution in the deep soil profile, N use efficiencies, functional gene abundances involving soil nitrification–denitrification processes and N2O production. Compared with the winter fallow, the maize yield significantly increased by 11.6% after 10 years of green manuring, and water storage in 0–200 cm soil profile significantly increased by 5.0–17.1% at maize seedling stage. The total N content in the soil layer at 0–90 cm increased by 15.8–19.7%, while the nitrate content in the deep soil layer (80–120 cm) decreased by 17.8–39.6%. Planting GM significantly increased the N recovery rate (10.4–32.7%) and fertilizer N partial productivity (4.6–13.3%). Additionally, the topsoil N functional genes (ammonia-oxidizing archaea amoA, ammonia-oxidizing bacterial amoA, nirS, nirK) significantly decreased without increasing N2O production potential. These results indicated that long-term planting of the deep-rooted GM effectively reduce the accumulation of nitrates in the deep soil and improve the crop yield and N use efficiencies, demonstrating a great value in green manuring to improve the fertility of the soil, increase the crop yield, and reduce the risk of N loss in NCP.